Ruby rice mill (solvent extraction method) - Lacdan, Jose Reyes; Dela Paz, Rolando de Leon.; Roman, Antonio Hieras (Diliman, Quezon City College of Engineering, 1969)
This market survey has been initiated primarily to determine the economic feasibility of a new method of milling rice which may augment, if not replace, the present kiskisan and cono mills. A revolutionary method of milling rice has been devised by Truman Wayne of the Riviana Research and Development. This process, called the Solvent Extraction Method (SEM), provides in one combined and continuous process rice, rice oil, and rice bran not heretofore available by conventional milling.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Rice trade; Rice products